The Effect of Perceptions of Sharia-Based Companies on Generation Z Students’ Employment Preferences: The Moderating Role of Religiosity - Abizar; Immawati Asniar; Nina Ramadhani Wulandari; Ahmad Noor Islahudin (Nuban Jagadhita Centre, 2026)
Purpose: The transformation of employment preferences in the digital economy has encouraged Generation Z to consider organizational values, ethical environments, and spiritual meaning alongside financial incentives. Although Islamic companies offer careers based on Sharia principles and ethical values, empirical studies on Generation Z’s employment preferences toward these organizations remain limited, particularly regarding the moderating role of religiosity. This study analyzes the influence of perceptions of Islamic companies on employment preferences and examines the moderating effect of religiosity using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. Methodology: A quantitative explanatory design was employed involving 99 Muslim Generation Z respondents aged 18–27 years in Bandar Lampung. Data were collected through purposive sampling using online and offline questionnaires. Findings: The findings reveal that perceptions of Islamic companies positively and significantly influence employment preferences, while religiosity both positively affects employment preferences and strengthens this relationship. This study offers a novel contribution by identifying religiosity as a moderating mechanism linking organizational perceptions to career preferences. It further enriches Islamic Human Resource Management and Islamic Economics literature by integrating Islamic organizational values with career decision-making and provides practical insights for strengthening Islamic human capital, developing the Islamic labor market, and supporting a sustainable halal economic ecosystem.